Pengujian Metalografi Dan Kekerasan Dalam Penentuan Umur Sisa Screen Tube Superheater Pada Boiler Batu Bara - Nurdiasyah, Nurdiansyah; Ratnawati, Ratnawati; Anoi, Yano Hanung; Yuono, Lukito Dwi (TURBO [Tulisan Riset Berbasis Online], 2025)
Superheater is one of the main parts of the boiler. One of the problems that often occurs in the superheater screen tube is that the screen bends due to exposure to high temperatures which causes the screen tube to deform. The aging phenomenon (decarburization) will occur over time the tube is operated, affecting the mechanical properties of the tube material, especially its hardness. The research objectives achieved are to determine the actual conditions, feasibility and remaining life of the superheater screen tube experiencing bending. Based on these conditions, it is necessary to conduct testing on the superheater screen tube that has been operating for approximately 11 years (96360 hours) until now. The method used is to conduct direct, macro and micro examinations on the condition of the screen tube that is bending. In situ metallographic testing on each superheater screen tube is carried out to determine the degradation of the high temperature effect during operation. In addition to in situ testing, metallographic testing in the laboratory is used to analyze the microstructure of the tube material during operation. Hardness testing, the chemical composition of the tube material is also carried out as a support in the process of calculating the remaining life using the Larson Miller Parameter (LMP) approach. From the test, the results showed that the condition of the screen tube that was bending was still suitable for use in accordance with the applicable SOP. In terms of microstructure, the superheater screen tube has experienced aging (decarburization) with a decrease in hardness value when compared to the hardness of the normal tube (166 HV). If operated properly, the superheater screen tube that is bending can be operated for up to 2 years and 8 months if the Turn Around (TA) program is not carried out until a replacement tube is available for 2 years and 10 months, still below the temperature (6200 C) or below the design temperature.